2019
DOI: 10.1155/2019/4036716
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Circumferential Heterotopic Ossification Discovered at the Base of a Loop Ileostomy

Abstract: Heterotopic ossification is a rare phenomenon defined by the formation of bone within nonossifying soft tissues. A rare variant of heterotopic ossification is heterotopic mesenteric ossification (HMO), in which there is involvement of the mesentery and surrounding intra-abdominal structures. There are only four previously reported cases of HMO involving an ileostomy. We present a case of HMO affecting an ileostomy which was discovered during elective stoma reversal in a 52-year-old male who required fecal dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…El diagnóstico de la OHI se basa en los hallazgos característicos por estudios de imágenes (lesiones de aspecto lineal y ramificado de alta densidad localizadas principalmente en el mesenterio), dentro del contexto clínico sugerente (varón de mediana edad con antecedentes quirúrgicos múltiples o traumáticos abdominales). Además, se ha demostrado que la elevación de la fosfatasa alcalina puede sugerir el diagnóstico junto con los factores antes descritos, debido a la actividad osteoblástica presente en esta patología 2 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El diagnóstico de la OHI se basa en los hallazgos característicos por estudios de imágenes (lesiones de aspecto lineal y ramificado de alta densidad localizadas principalmente en el mesenterio), dentro del contexto clínico sugerente (varón de mediana edad con antecedentes quirúrgicos múltiples o traumáticos abdominales). Además, se ha demostrado que la elevación de la fosfatasa alcalina puede sugerir el diagnóstico junto con los factores antes descritos, debido a la actividad osteoblástica presente en esta patología 2 .…”
Section: Discussionunclassified
“…La osificación heterotópica intraabdominal (OHI) es un proceso benigno que consiste en la formación de tejido óseo en sitios no habituales dentro del abdomen. Ocurre sobre todo en el mesenterio, la pared abdominal y el omento, pero se han reportado casos en cicatriz quirúrgica 1 , asa de ileostomía 2 , reparaciones con malla de hernias 3 y apófisis xifoide 4 .…”
Section: Introductionunclassified
“…The main clinical significance for recognizing HMO is its complications, such as small bowel obstruction, ileus, abortion of surgical procedure due to extensive involvement of mesenteric vasculature [ 5 , 8 , 17 , 25 ], and its differential diagnosis from malignancies such as peritoneal carcinomatosis which is important due to relevance in clinical management. Other differential diagnoses include dystrophic calcification (no osteoblasts), leakage of contrast, and foreign materials [ 12 , 13 , 17 , 22 , 24 ]. Clinical management of HMO depends on the presence of symptoms and complications.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical procedure to remove the HMO might be necessary for symptomatic patients or for those with severe complications such as ileus or obstruction. Invasive treatment is considered unnecessary for asymptomatic patients [ 17 ]. Noninvasive treatments, such as non-steroidal anti-inflammatory drugs (e.g., ibuprofen, indomethacin), diphosphonates (etidronate), or radiation therapy have been reported in early studies [ 2 , 7 , 10 ], but are rarely seen in recent literature [ 13 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a large proportion of case reports, heterotopic mesenteric ossification is described as a sequela of abdominal surgery, commonly presenting with obstructive symptoms (Table 1). 14–42 Some have suggested that small regions of ossification may not be a rare complication of surgery 3 . Other risk factors for developing heterotopic mesenteric ossification include trauma, such as fractures, blunt injury, burns, and spinal cord or brain injuries 10 .…”
Section: Discussionmentioning
confidence: 99%